Deep Vein Thrombosis and Pulmonary Embolism Among Patients With a Cryptogenic Stroke Linked to Patent Foramen Ovale—A Review of the Literature - Zietz, Annaelle; Sutter, Raoul; De Marchis, Gian Marco (Frontiers in Neurology, 2020)
Background: Venous thromboembolism (VTE) can occur simultaneously with a cryptogenic stroke (CS) linked to patent foramen ovale (PFO), given paradox thromboembolism as potential stroke cause. However, little is known on the frequency of concomitant VTE and CS. We aimed to review the literature on the frequency of VTE in patients with CS linked to PFO (primary aim) and of ischemic stroke among patients with pulmonary embolism (PE) (secondary aim). Methods: We performed a Medline search for cohort studies, written in English, with the following characteristics: (a) enrolling patients hospitalized for an acute ischemic stroke undergoing a work-up for deep venous thrombosis (DVT) and/or PE. To be included in this review, a study had to have at least a subgroup of patients with PFO; (b) the time interval between the index stroke and the work-up had to be within 40 days and the studies had to differentiate between DVT and PE. For the secondary aim, studies had to include patients with acute PE, known PFO-status and routine brain imaging on admission or within one year. Results: We found eight studies reporting on the frequency of VTE after an acute CS linked to PFO. Concerning DVT, the reported frequency ranged between 7 % and 27.0%; concerning PE, it lied around 4,4 to 37%. Five studies assessed the frequency of ischemic brain lesions among patients with an acute PE. In all studies, the presence of PFO was associated with ischemic brain lesions, both at baseline and follow-up. Conclusion: VTE can be detected in patients with CS linked to PFO. While routine screening for VTE in patients with CS linked to PFO does not appear justified, history taking and clinical exam should consider concomitant VTE. Whenever clinically suspected, the threshold to trigger ancillary testing for VTE should be low. Among patients with an acute PE linked to PFO, vigilance for new neurologic deficits should be increased, with a low threshold for brain imaging.